Collage Principle : Exhibition Documentation - Exhibition Originals. (Stuttgart : Institut für Auslandbeziehungen, 1982)
Beuys, Joseph ; Borneff, Karl F. ; Brodwolf, Jürgen ; Ebehalt, Wolfgang ; Gerz, Jochen ; Gessinger, Matthias ; Hirscher, Heinz E. ; Hoehme, Gerhard ; Hüppi, Alfonso ; Janz, Angelika ; Kaufmann, Herbert ; Köthe, Fitz ; Kolar, Jiri ; Kreuzhage, Werner ; Mon, Franz ; Munsky, Miriam ; Rungenhagen, Ulf ; Schenk, Michael ; Schreiter, Johannes ; Schultze, Bernard ; Söllner, Max ; Sorge, Peter ; Vostell, Wolf
Collage Principle : Exhibition Documentation - Exhibition Originals, Institut für Auslandbeziehungen, Stuttgart, 1982
kunstcatalogus